Preparation method of modified zinc oxide nano-particles as well as product and application of modified zinc oxide nano-particles

Modified zinc oxide nanoparticles were prepared through solvothermal reaction and surface modification, and combined with chemical reaction and photocatalytic aldehyde removal mechanism, the shortcomings of existing formaldehyde removal technology were solved and efficient and long-lasting aldehyde removal effect was achieved.

CN119569104APending Publication Date: 2025-03-07SHANGHAI NAT ENG RES CENT FORNANOTECH

Patent Information

Application Number
CN202411831075.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

There are various shortcomings in the existing formaldehyde removal technology, including slow plant absorption effect, physical adsorption saturation and secondary pollution problems, chemical reaction saturation and high catalyst cost, photocatalytic degradation nanometal oxides are prone to agglomeration and inactivation, resulting in a decrease in degradation efficiency.

Method used

Modified zinc oxide nanoparticles are prepared by solvent-thermal reaction and surface modification methods. Combined with the chemical reaction of organic amine substances, the advantages of photocatalytic degradation of aldehydes and inorganic nanoparticles, the silicone groups on the surface of modified zinc oxide nanoparticles improve hydrophobicity, inhibit dust adhesion and damage aldehyde removal performance.

Benefits of technology

It achieves an efficient and long-lasting aldehyde removal effect. Combining the advantages of chemical reactions and photocatalysis, modified zinc oxide nanoparticles can effectively reduce formaldehyde concentration and show long-term aldehyde removal performance in pollution resistance tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a preparation method of modified zinc oxide nanoparticles as well as a product and application thereof, the preparation method comprises two steps of solvothermal reaction and surface modification, combines the advantages of chemical reaction formaldehyde removal of organic amine substances and photocatalytic degradation formaldehyde removal of inorganic nanoparticles, and has the characteristic of efficient formaldehyde removal. Siloxane groups on the surfaces of the modified zinc oxide nanoparticles effectively improve the hydrophobicity of the surfaces of the zinc oxide nanoparticles, and prevent dust in air from being attached to damage the formaldehyde removal performance, so that the formaldehyde removal function is played for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of daily chemical industry, and specifically relates to a preparation method of modified zinc oxide nanoparticles and a product and application thereof. Background Art

[0002] Materials such as plywood, laminate flooring, doors, wardrobes, and cabinets used in home decoration will emit formaldehyde. Due to the special irritating smell of formaldehyde, the human body will experience various discomfort symptoms when exposed to a certain concentration of formaldehyde gas. The national standard GB50325-2020 "Code for Indoor Environmental Pollution Control of Civil Construction Engineering" stipulates that the concentration of formaldehyde in the indoor environment must be less than 0.08mg / m 3 . Commonly used methods for removing formaldehyde from indoor environments include plant absorption, physical adsorption, chemical reaction, thermal catalytic oxidation, photocatalytic degradation, plasma, etc. At present, various methods for removing formaldehyde have advantages and disadvantages, so they are all used in actual formaldehyde removal scenarios. Plants are green and environmentally friendly, but the absorption effect is slow. The physical adsorption method is easy to operate, but there are problems of adsorption saturation and secondary pollution. The chemical reaction method uses the direct chemical reaction of active amino groups with formaldehyde, and the immediate formaldehyde removal effect is significant, but there is also the problem of reaction saturation. At the same time, during the storage process, the active amino group will react with acidic gases such as carbon dioxide in the environment and be gradually consumed, thereby losing the formaldehyde removal performance. The thermal catalytic oxidation method is energy-saving and environmentally friendly, and has high degradation efficiency, but it requires the use of precious metals such as Pt, Au, Pd, and Ir as catalysts, which is expensive. The photocatalytic degradation method can completely degrade formaldehyde into carbon dioxide and water, but the nano-metal oxides used as photocatalysts are prone to agglomeration and inactivation, resulting in a decrease in degradation efficiency. It can be seen that the development of a composite mechanism formaldehyde removal product will have a high market prospect. The patent with application number 202110937895.1 discloses a formaldehyde remover, which adopts a composite formula and contains a variety of effective formaldehyde removal ingredients, such as biodegradable enzymes, organic matter A and photocatalysts. Among them, organic matter A is an organic acid or an organic base. The composite formula of the formaldehyde remover is merely a physical mixture of formaldehyde removal substances with different formaldehyde removal mechanisms, and fails to exert its synergistic function. Summary of the invention

[0003] The present invention aims to provide a method for preparing modified zinc oxide nanoparticles.

[0004] Another object of the present invention is to provide a siliceous body product encapsulated with IR780@ prepared by the above method.

[0005] Another object of the present invention is to provide an application of the above product.

[0006] The object of the present invention is achieved by the following scheme: A method for preparing modified zinc oxide nanoparticles, comprising the following steps: (1) Solvothermal reaction The temperature of a 0.5-1.0 mol / L zinc nitrate solution is raised to 60-80°C, and an equal volume of sodium carbonate solution is added dropwise under stirring, wherein the molar concentration ratio of the sodium carbonate solution to the zinc nitrate solution is 1-1.2:1.0, and stirring is continued for 30-60 min to obtain a white precipitate, and the precipitate product is filtered to obtain a basic zinc carbonate powder; the basic zinc carbonate powder is dispersed in a low-carbon diol solvent, wherein the mass ratio of the basic zinc carbonate powder to the low-carbon diol is 10.0-15.0:100.0, and ultrasonic dispersion is performed to obtain a mixture; The mixture was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, with a filling degree of 65-80%. The autoclave was placed in an oven and reacted at 180-220°C for 12-16 h. After the reaction, the reaction product was cooled to room temperature. The reaction product was washed with water and ethanol for 3 times, respectively, and filtered to obtain wet powder of zinc oxide nanoparticles. The wet powder was placed in an oven and baked at 60-80°C for 10-12 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain zinc oxide nanoparticles containing alcohol hydroxyl groups on the surface. (2) Surface modification Deionized water and nonionic surfactant isotridecyl alcohol polyoxyethylene ether (E0=8) are mixed evenly, and then acrylic acid monomer is added. Deionized water and nonionic surfactant isotridecyl alcohol polyoxyethylene ether (E0=8) are mixed evenly, and then acrylic acid monomer is added. The acrylic acid monomer is polyethylene glycol 400 monoacrylate, triisopropylsilyl methacrylate and a-amino ethyl acrylate. The mass ratio of polyethylene glycol 400 monoacrylate, triisopropylsilyl methacrylate and a-amino ethyl acrylate is 1-3:1-3:1. Stir evenly to prepare a pre-emulsion for later use. In another reaction container, add a certain amount of deionized water, isomeric tridecanol polyoxyethylene ether (E0=8) and NH4HCO3 powder, add the surface alcohol hydroxyl group-containing zinc oxide nanoparticles prepared in step (1) under stirring, heat to 65-85°C, continue stirring, add a certain amount of pre-emulsion and an aqueous solution of initiator ammonium persulfate, react at constant temperature for 30-40 min to obtain a prepolymer, add the remaining pre-emulsion within 3 h, keep the temperature for reaction for 1-2 h after the addition is complete, cool to room temperature, wash the reaction product with water and ethanol for 3 times, filter to obtain wet powder of modified zinc oxide nanoparticles, put the wet powder into an oven and bake at 60-80°C for 10-12 h to obtain dry powder, grind the dry powder with an agate mortar to obtain modified zinc oxide nanoparticles.

[0007] The acrylic monomers are triisopropylsilyl methacrylate, a-aminoethyl acrylate and polyethylene glycol 400 monoacrylate.

[0008] The structural formula of polyethylene glycol 400 monoacrylate is: The alcoholic hydroxyl group of the monomer undergoes an etherification reaction with zinc oxide nanoparticles containing alcoholic hydroxyl groups on the surface, thereby bonding to the surface of the zinc oxide nanoparticles.

[0009] The structural formula of triisopropylsilyl methacrylate is: The silane group in the monomer effectively improves the hydrophobicity of the surface of zinc oxide nanoparticles, reducing the gradual damage to the formaldehyde removal performance due to the adhesion of dust in the air.

[0010] The structural formula of ethyl aminoacrylate is: The monomer contains active amino groups, which can react chemically with formaldehyde to eliminate formaldehyde quickly and efficiently.

[0011] The mass ratio of the triisopropylsilyl methacrylate, a-aminoethyl acrylate and polyethylene glycol 400 monoacrylate is 1-3:1-3:1.

[0012] The moles of the zinc nitrate solution.

[0013] The low-carbon diol is one of ethylene glycol, 1,3-propylene glycol and 1,4-butanediol.

[0014] The present invention provides a modified zinc oxide nanoparticle, which is characterized in that it is prepared according to any of the above methods.

[0015] The invention provides an application of modified zinc oxide nanoparticles as a formaldehyde removal agent, which has a high-efficiency and lasting formaldehyde removal effect.

[0016] It combines the advantages of chemical reaction of organic amine substances to remove formaldehyde and photocatalytic degradation of inorganic nanoparticles to remove formaldehyde, and has high efficiency in removing formaldehyde. The siloxane groups on the surface of modified zinc oxide nanoparticles effectively improve the hydrophobicity of the surface of zinc oxide nanoparticles, inhibit the adhesion of dust in the air to damage the formaldehyde removal performance, and thus exert the formaldehyde removal function for a long time.

[0017] Compared with the prior art, the modified zinc oxide nanoparticles of the present invention have the following advantages as formaldehyde scavengers: 1. It combines the advantages of chemical reaction of organic amines to remove formaldehyde and photocatalytic degradation of inorganic nanoparticles to remove formaldehyde, and has high efficiency in removing formaldehyde.

[0018] 2. The siloxane groups on the surface of modified zinc oxide nanoparticles effectively improve the hydrophobicity of the surface of zinc oxide nanoparticles, inhibit the adhesion of dust in the air to damage the formaldehyde removal performance, thereby exerting the formaldehyde removal function for a long time. DETAILED DESCRIPTION

[0019] The technical solution of the present invention is further described below according to specific embodiments. The protection scope of the present invention is not limited to the following embodiments, which are listed only for illustrative purposes and do not limit the present invention in any way.

[0020] Example 1 A modified zinc oxide nanoparticle is prepared by solvent thermal reaction and surface modification according to the following steps: (1) Solvothermal reaction Heat 50 mL of 0.5 mol / L zinc nitrate solution to 60°C, add 50 mL of 0.5 mol / L sodium carbonate solution dropwise under stirring, and continue stirring for 60 min to obtain a white precipitate. Filter the white precipitate, wash the precipitate with distilled water and anhydrous ethanol for 3 times, and dry it in a 100°C oven for 6 h to obtain basic zinc carbonate powder. Disperse 10.0 g of basic zinc carbonate powder in 100.0 g of ethylene glycol, and disperse uniformly by ultrasonication to obtain a mixture; The mixture was transferred to a 150 mL polytetrafluoroethylene-lined stainless steel autoclave, and the autoclave was placed in an oven for reaction at 180 °C for 16 h. After the reaction was completed, the reaction product was cooled to room temperature, and the reaction product was washed with water and ethanol for 3 times, respectively, and filtered to obtain wet powder of zinc oxide nanoparticles. The wet powder was placed in an oven and baked at 60 °C for 12 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain zinc oxide nanoparticles containing alcohol hydroxyl groups on the surface. (2) Surface modification In a 250 ml reactor equipped with a stirrer, 44.0 g of water was added, and then 1.0 g of isomeric tridecanol polyoxyethylene ether (EO=8) was added and mixed evenly, and then 2.0 g of polyethylene glycol 400 monoacrylate was added. After stirring for 5 min, 6.0 g of triisopropylsilyl methacrylate and 2.0 g of ethyl a-aminoacrylate were added under stirring, and stirred for 30 min to prepare a pre-emulsion for standby use; In another 250 ml four-necked flask equipped with a stirrer, a thermometer and a condenser, 31.1 g of water, 0.5 g of isomeric tridecanol polyoxyethylene ether (EO=8) and 0.3 g of NH4HCO3 were added, and 10.0 g of the surface alcohol hydroxyl zinc oxide nanoparticles prepared in step (1) were added under stirring. The nanoparticles were placed in a water bath and heated to 80°C. 5.0 g of the pre-emulsion and an aqueous solution of 0.1 g of ammonium persulfate dissolved in 3.0 g of water were added to the reactor, and stirred and kept warm for 30 min to obtain a prepolymer. The remaining pre-emulsion was dripped into the reactor within 3 hours while keeping stirring and constant temperature. After the addition was completed, the reaction was kept warm for 1 hour and then cooled to room temperature. The reaction product was washed with water and ethanol for 3 times respectively, and filtered to obtain modified zinc oxide nanoparticle wet powder. The wet powder was placed in an oven and baked at 60 °C for 12 hours to obtain dry powder. The dry powder was ground with an agate mortar to obtain modified zinc oxide nanoparticles.

[0021] Example 2 A modified zinc oxide nanoparticle is prepared according to the following steps: (1) Solvothermal reaction 50 mL of 0.75 mol / L zinc nitrate solution was heated to 70 °C, and 50 mL of 0.825 mol / L sodium carbonate solution was added dropwise to the zinc nitrate solution under stirring, and the stirring was continued for 45 min to obtain a white precipitate, and the precipitate was filtered, and the precipitate was washed with distilled water and anhydrous ethanol for 3 times, and then the precipitate was placed in a 110 °C oven and dried for 4.5 h to obtain basic zinc carbonate powder; 12.5 g of basic zinc carbonate powder was dispersed in 100.0 g of 1,3-propylene glycol, and ultrasonically dispersed to obtain a mixture; The mixture was transferred to a 150 mL polytetrafluoroethylene-lined stainless steel autoclave, and the autoclave was placed in an oven for reaction at 200 °C for 14 h. After the reaction was completed, the reaction product was cooled to room temperature, and the obtained reaction product was washed with water and ethanol for 3 times, respectively, and filtered to obtain wet powder of zinc oxide nanoparticles. The wet powder was placed in an oven and baked at 70 °C for 11 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain zinc oxide nanoparticles containing alcohol hydroxyl groups on the surface. (2) Surface modification In a 250 ml reactor equipped with a stirrer, 44.0 g of water was added, 1.0 g of isomeric tridecanol polyoxyethylene ether (EO=8) was added and mixed, and then 3.0 g of polyethylene glycol 400 monoacrylate was added. After stirring for 5 min, 4.0 g of triisopropylsilyl methacrylate and 4.0 g of ethyl a-aminoacrylate were added under stirring, and stirred for 30 min to prepare a pre-emulsion for standby use; In another 250 ml four-necked flask equipped with a stirrer, a thermometer, and a condenser, add 31.1 g of water, 0.5 g of isomeric tridecanol polyoxyethylene ether (EO=8), and 0.3 g of NH4HCO3, add 10.0 g of the surface alcohol hydroxyl zinc oxide nanoparticles prepared in step (1) under stirring, place it in a water bath and heat it to 80°C, take 5.0 g of the pre-emulsion and an aqueous solution of 0.1 g of ammonium persulfate dissolved in 3.0 g of water and add them to the reactor, stir and keep warm for 30 min; The remaining pre-emulsion was dripped into the reactor within 3 hours while keeping stirring and constant temperature. After the addition was completed, the reaction was kept warm for 1 hour and then cooled to room temperature. The reaction product was washed with water and ethanol for 3 times respectively, and filtered to obtain modified zinc oxide nanoparticle wet powder. The wet powder was placed in an oven and baked at 70 °C for 10 hours to obtain dry powder. The dry powder was ground with an agate mortar to obtain modified zinc oxide nanoparticles.

[0022] Example 3 A zinc oxide nanoparticle is prepared according to the following steps: (1) Solvothermal reaction 50 mL of 1.0 mol / L zinc nitrate solution was heated to 80 °C, and 50 mL of 1.2 mol / L sodium carbonate solution was added dropwise to the zinc nitrate solution under stirring, and the stirring was continued for 30 min to obtain a white precipitate. The precipitate was filtered, and the precipitate was washed with distilled water and anhydrous ethanol for 3 times, and then dried in a 120 °C oven for 3 h to obtain basic zinc carbonate powder; 15.0 g of basic zinc carbonate powder was dispersed in 100.0 g of 1,4-butanediol, and ultrasonically dispersed to obtain a mixture; The mixture was transferred to a 150 mL polytetrafluoroethylene-lined stainless steel autoclave, and the autoclave was placed in an oven for reaction at 220 °C for 12 h. After the reaction was completed, the reaction product was cooled to room temperature, and the obtained reaction product was washed with water and ethanol for 3 times, respectively, and filtered to obtain wet powder of zinc oxide nanoparticles. The wet powder was placed in an oven and baked at 80 °C for 10 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain zinc oxide nanoparticles containing alcohol hydroxyl groups on the surface. (2) Surface modification In a 250 ml reactor equipped with a stirrer, add 44.0 g of water, add 1.0 g of isomeric tridecanol polyoxyethylene ether (EO=8) and mix well, then add 2.0 g of polyethylene glycol 400 monoacrylate, stir for 5 min, then add 2.0 g of triisopropylsilyl methacrylate and 6.0 g of ethyl a-aminoacrylate under stirring, stir for 30 min to prepare a pre-emulsion for standby use; In another 250 ml four-necked flask equipped with a stirrer, a thermometer, and a condenser, add 31.1 g of water, 0.5 g of isomeric tridecanol polyoxyethylene ether (EO=8), and 0.3 g of NH4HCO3, add 10.0 g of the surface alcohol hydroxyl zinc oxide nanoparticles prepared in step (1) under stirring, place it in a water bath and heat it to 80°C, take 5.0 g of the pre-emulsion and an aqueous solution of 0.1 g of ammonium persulfate dissolved in 3.0 g of water and add them to the reactor, stir and keep warm for 30 min; The remaining pre-emulsion was dripped into the reactor within 3 hours while keeping stirring and constant temperature. After the addition was completed, the reaction was kept warm for 1 hour and then cooled to room temperature. The reaction product was washed with water and ethanol for 3 times respectively, and filtered to obtain modified zinc oxide nanoparticle wet powder. The wet powder was placed in an oven and baked at 70 °C for 10 hours to obtain dry powder. The dry powder was ground with an agate mortar to obtain modified zinc oxide nanoparticles.

[0023] Comparative Example 1 Comparative Example 1: Modified zinc oxide nanoparticles were prepared according to the following steps: Step (1) solvothermal reaction, same as step (1) of Example 2; In step (2) of surface modification, 3.0 g of polyethylene glycol 400 monoacrylate in step (2) of Example 2 was replaced by deionized water, and the masses of the remaining additives and the reaction steps were the same as those in step (2) of Example 1.

[0024] Comparative Example 2 Comparative Example 2: Modified zinc oxide nanoparticles were prepared according to the following steps: Step (1) Solvothermal reaction is the same as step (1) of Example 2; In the surface modification step (2), 4.0 g of triisopropylsilyl methacrylate in step (2) of Example 2 was replaced by deionized water, and the masses of the remaining additives and the reaction steps were the same as those in step (2) of Example 2.

[0025] Comparative Example 3 Modified zinc oxide nanoparticles were prepared according to the following steps: Step (1) Solvothermal reaction is the same as step (1) of Example 2; In the surface modification step (2), 4.0 g of ethyl a-aminoacrylate in step (2) of Example 2 was replaced by deionized water, and the masses of the remaining additives and the reaction steps were the same as those in step (2) of Example 2.

[0026] Comparative Example 4 Modified zinc oxide nanoparticles were prepared according to the following steps: The surface-containing alcohol hydroxyl group-containing zinc oxide nanoparticles prepared in step (1) of Example 2 were used as modified zinc oxide nanoparticles.

[0027] 1.0 g of the modified zinc oxide nanoparticles prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were weighed and dispersed in 100.0 mL of deionized water. Ultrasonic dispersion at a power of 250 W was used for 10 min to obtain a formaldehyde removal agent dispersion, and performance testing was performed.

[0028] Formaldehyde removal performance test The formaldehyde removal performance test was carried out according to the industry standard QB / T 2761-2006 "Test Method for Purification Effect of Indoor Purification Products". The specific method is: spray 100.0 mL of the formaldehyde remover dispersion prepared above on the base paper three times (wait until the liquid sprayed last time is dry before spraying the next time), and immediately hang it in the test chamber B after drying. Hang the untreated base paper in the blank chamber A. Place containers containing the same formaldehyde release source in the test chamber and the blank chamber respectively, and close the cabin door immediately. Turn on the fans in the test chamber and the blank chamber, stir for 1 min, so that the air in the chamber and the formaldehyde released by the release source are evenly mixed, and then turn off the fan. Use a nationally certified formaldehyde detector (CMA level) to test the formaldehyde concentration in the blank chamber as the initial concentration C0. After 24 hours, the formaldehyde concentrations in the test chamber and the blank chamber are tested again to evaluate the formaldehyde removal effect of the formaldehyde remover, and the removal rate y=(C A -C B ) / C A *100.

[0029] Pollution resistance test The operation of the pollution resistance test is similar to the formaldehyde removal performance test, except that the base paper sprayed with the formaldehyde removal dispersion is placed indoors for 30 days before being placed in the test chamber for formaldehyde removal performance test. The 24-hour formaldehyde removal rates of the formaldehyde removal agent dispersions prepared by the modified zinc oxide nanoparticles in Examples 1 to 3 were all above 98%, showing a highly efficient formaldehyde removal effect. Comparative Example 4 is a formaldehyde removal agent dispersion prepared by directly using solvent thermal reaction to prepare zinc oxide nanoparticles containing alcohol hydroxyl groups on the surface, and the 24-hour formaldehyde removal rate is 89.8%. The formaldehyde removal rate of Comparative Example 1 is close to that of Comparative Example 4, because polyethylene glycol 400 monoacrylate monomer is not added in step (2) of surface modification, and no reactive monomer reacts with the surface-containing alcohol hydroxyl zinc oxide nanoparticles, and the prepared acrylic copolymer fails to bind to the surface of the zinc oxide nanoparticles. The formaldehyde removal rate of Comparative Example 2 is close to that of Example 2. The formaldehyde removal rate of Comparative Example 3 is close to that of Comparative Example 4, because a-amino ethyl acrylate monomer is not added in step (2) of surface modification, and the modified zinc oxide nanoparticles obtained do not have a chemical formaldehyde removal effect. In the pollution resistance test, after 30 days of indoor placement, the 24 h formaldehyde removal rate of the formaldehyde removal agent dispersion prepared by the modified zinc oxide nanoparticles of Examples 1 to 3 decreased slightly, while that of Comparative Examples 2 and 4 decreased significantly. The above shows that the modified zinc oxide nanoparticles of the examples showed high efficiency and long-lasting effect when used as formaldehyde removal agents.

[0030] Those skilled in the art should note that the embodiments described in the present invention are merely exemplary, and various other substitutions, changes and improvements may be made within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but only to the claims.

Claims

1. A method for preparing modified zinc oxide nanoparticles, characterized in that: The process includes solvothermal reaction and surface modification, and comprises the following steps: (1) Solvothermal reaction The zinc nitrate solution with a concentration of 0.5-1.0 mol / L is heated to 60-80°C, and an equal volume of sodium carbonate solution is added dropwise under stirring, the molar concentration ratio of the sodium carbonate solution to the zinc nitrate solution is 1-1.2:1.0, and the stirring is continued for 30-60 minutes to obtain a white precipitate, and the white precipitate product is filtered to obtain basic zinc carbonate powder; the basic zinc carbonate powder is dispersed in a low-carbon diol solvent, so that the mass ratio of the basic zinc carbonate powder to the low-carbon diol is (10.0-15.0):100, and a mixture is uniformly dispersed by ultrasonication; The mixture was transferred to a polytetrafluoroethylene-lined stainless steel autoclave with a filling degree of 65-80%, and the reaction was carried out at 180-220°C for 12-16 h. After the reaction was completed, the mixture was cooled to room temperature. The reaction product was washed with water and ethanol for 3 times, respectively, and filtered to obtain wet powder of zinc oxide nanoparticles. The wet powder was placed in an oven and baked at 60-80°C for 10-12 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain zinc oxide nanoparticles containing alcohol hydroxyl groups on the surface. (2) Surface modification Deionized water and nonionic surfactant isotridecyl alcohol polyoxyethylene ether (E0=8) are mixed evenly, and then acrylic acid monomers are added, wherein the acrylic acid monomers are polyethylene glycol 400 monoacrylate, triisopropylsilyl methacrylate and ethyl a-aminoacrylate, and the mass ratio of polyethylene glycol 400 monoacrylate, triisopropylsilyl methacrylate and ethyl a-aminoacrylate is 1-3:1-3:1, and the mixture is stirred evenly to prepare a pre-emulsion for later use; In another reaction container, deionized water, isomeric tridecanol polyoxyethylene ether (E0=8) and NH4HCO3 powder are added, and the surface alcohol hydroxyl group-containing zinc oxide nanoparticles prepared in step (1) are added under stirring, and the mixture is heated to 65-85°C, and stirred continuously. The pre-emulsion and the aqueous solution of initiator ammonium persulfate are added, and the prepolymer is reacted at a constant temperature for 30-40 min. The remaining pre-emulsion is added within 3 h. After the addition is completed, the mixture is kept warm for 1-2 h, and then cooled to room temperature. The reaction product is washed with water and ethanol for 3 times, and filtered to obtain wet powder of modified zinc oxide nanoparticles. The wet powder is placed in an oven and baked at 60-80°C for 10-12 h to obtain dry powder. The dry powder is ground with an agate mortar to obtain modified zinc oxide nanoparticles.

2. The method for preparing modified zinc oxide nanoparticles according to claim 1, characterized in that: The low-carbon diol is one of ethylene glycol, 1,3-propylene glycol and 1,4-butanediol.

3. The method for preparing modified zinc oxide nanoparticles according to claim 1 or 2, characterized in that: Prepare as follows: (1) Solvothermal reaction Heat 50 mL of 0.5 mol / L zinc nitrate solution to 60°C, add 50 mL of 0.5 mol / L sodium carbonate solution dropwise under stirring, and continue stirring for 60 min to obtain a white precipitate. Filter the white precipitate, wash the precipitate with distilled water and anhydrous ethanol for 3 times, and dry it in a 100°C oven for 6 h to obtain basic zinc carbonate powder. Disperse 10.0 g of basic zinc carbonate powder in 100.0 g of ethylene glycol, and disperse uniformly by ultrasonication to obtain a mixture; The mixture was transferred to a 150 mL polytetrafluoroethylene-lined stainless steel autoclave, and the autoclave was placed in an oven for reaction at 180 °C for 16 h. After the reaction was completed, the reaction product was cooled to room temperature, and the reaction product was washed with water and ethanol for 3 times, respectively, and filtered to obtain wet powder of zinc oxide nanoparticles. The wet powder was placed in an oven and baked at 60 °C for 12 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain zinc oxide nanoparticles containing alcohol hydroxyl groups on the surface. (2) Surface modification In a 250 ml reactor equipped with a stirrer, 44.0 g of water was added, and then 1.0 g of isomeric tridecanol polyoxyethylene ether (EO=8) was added and mixed evenly, and then 2.0 g of polyethylene glycol 400 monoacrylate was added. After stirring for 5 min, 6.0 g of triisopropylsilyl methacrylate and 2.0 g of ethyl a-aminoacrylate were added under stirring, and stirred for 30 min to prepare a pre-emulsion for standby use; In another 250 ml four-necked flask equipped with a stirrer, a thermometer and a condenser, 31.1 g of water, 0.5 g of isomeric tridecanol polyoxyethylene ether (EO=8) and 0.3 g of NH4HCO3 were added, and 10.0 g of the surface alcohol hydroxyl zinc oxide nanoparticles prepared in step (1) were added under stirring. The nanoparticles were placed in a water bath and heated to 80°C. 5.0 g of the pre-emulsion and an aqueous solution of 0.1 g of ammonium persulfate dissolved in 3.0 g of water were added to the reactor, and stirred and kept warm for 30 min to obtain a prepolymer. The remaining pre-emulsion was dripped into the reactor within 3 hours while keeping stirring and constant temperature. After the addition was completed, the reaction was kept warm for 1 hour and then cooled to room temperature. The reaction product was washed with water and ethanol for 3 times respectively, and filtered to obtain modified zinc oxide nanoparticle wet powder. The wet powder was placed in an oven and baked at 60 °C for 12 hours to obtain dry powder. The dry powder was ground with an agate mortar to obtain modified zinc oxide nanoparticles.

4. The method for preparing modified zinc oxide nanoparticles according to claim 1 or 2, characterized in that: Prepare as follows: (1) Solvothermal reaction 50 mL of 0.75 mol / L zinc nitrate solution was heated to 70 °C, and 50 mL of 0.825 mol / L sodium carbonate solution was added dropwise to the zinc nitrate solution under stirring, and the stirring was continued for 45 min to obtain a white precipitate. The precipitate was filtered, and the precipitate was washed with distilled water and anhydrous ethanol for 3 times, and then the precipitate was placed in a 110 °C oven and dried for 4.5 h to obtain basic zinc carbonate powder; 12.5 g of basic zinc carbonate powder was dispersed in 100.0 g of 1,3-propylene glycol, and ultrasonically dispersed to obtain a mixture; The mixture was transferred to a 150 mL polytetrafluoroethylene-lined stainless steel autoclave, and the autoclave was placed in an oven for reaction at 200 °C for 14 h. After the reaction was completed, the reaction product was cooled to room temperature, and the obtained reaction product was washed with water and ethanol for 3 times, respectively, and filtered to obtain wet powder of zinc oxide nanoparticles. The wet powder was placed in an oven and baked at 70 °C for 11 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain zinc oxide nanoparticles containing alcohol hydroxyl groups on the surface. (2) Surface modification In a 250 ml reactor equipped with a stirrer, 44.0 g of water was added, 1.0 g of isomeric tridecanol polyoxyethylene ether (EO=8) was added and mixed, and then 3.0 g of polyethylene glycol 400 monoacrylate was added. After stirring for 5 min, 4.0 g of triisopropylsilyl methacrylate and 4.0 g of ethyl a-aminoacrylate were added under stirring, and stirred for 30 min to prepare a pre-emulsion for standby use; In another 250 ml four-necked flask equipped with a stirrer, a thermometer, and a condenser, add 31.1 g of water, 0.5 g of isomeric tridecanol polyoxyethylene ether (EO=8), and 0.3 g of NH4HCO3, add 10.0 g of the surface alcohol hydroxyl zinc oxide nanoparticles prepared in step (1) under stirring, place it in a water bath and heat it to 80°C, take 5.0 g of the pre-emulsion and an aqueous solution of 0.1 g of ammonium persulfate dissolved in 3.0 g of water and add them to the reactor, stir and keep warm for 30 min; The remaining pre-emulsion was dripped into the reactor within 3 hours while keeping stirring and constant temperature. After the addition was completed, the reaction was kept warm for 1 hour and then cooled to room temperature. The reaction product was washed with water and ethanol for 3 times respectively, and filtered to obtain modified zinc oxide nanoparticle wet powder. The wet powder was placed in an oven and baked at 70 °C for 10 hours to obtain dry powder. The dry powder was ground with an agate mortar to obtain modified zinc oxide nanoparticles.

5. The method for preparing modified zinc oxide nanoparticles according to claim 1 or 2, characterized in that: Prepare as follows: (1) Solvothermal reaction 50 mL of 1.0 mol / L zinc nitrate solution was heated to 80 °C, and 50 mL of 1.2 mol / L sodium carbonate solution was added dropwise to the zinc nitrate solution under stirring, and the stirring was continued for 30 min to obtain a white precipitate. The precipitate was filtered, and the precipitate was washed with distilled water and anhydrous ethanol for 3 times, and then dried in a 120 °C oven for 3 h to obtain basic zinc carbonate powder; 15.0 g of basic zinc carbonate powder was dispersed in 100.0 g of 1,4-butanediol, and ultrasonically dispersed to obtain a mixture; The mixture was transferred to a 150 mL polytetrafluoroethylene-lined stainless steel autoclave, and the autoclave was placed in an oven for reaction at 220 °C for 12 h. After the reaction was completed, the reaction product was cooled to room temperature, and the obtained reaction product was washed with water and ethanol for 3 times, respectively, and filtered to obtain wet powder of zinc oxide nanoparticles. The wet powder was placed in an oven and baked at 80 °C for 10 h to obtain dry powder. The dry powder was ground with an agate mortar to obtain zinc oxide nanoparticles containing alcohol hydroxyl groups on the surface. (2) Surface modification In a 250 ml reactor equipped with a stirrer, add 44.0 g of water, add 1.0 g of isomeric tridecanol polyoxyethylene ether (EO=8) and mix well, then add 2.0 g of polyethylene glycol 400 monoacrylate, stir for 5 min, then add 2.0 g of triisopropylsilyl methacrylate and 6.0 g of ethyl a-aminoacrylate under stirring, stir for 30 min to prepare a pre-emulsion for standby use; In another 250 ml four-necked flask equipped with a stirrer, a thermometer, and a condenser, add 31.1 g of water, 0.5 g of isomeric tridecanol polyoxyethylene ether (EO=8), and 0.3 g of NH4HCO3, add 10.0 g of the surface alcohol hydroxyl zinc oxide nanoparticles prepared in step (1) under stirring, place it in a water bath and heat it to 80°C, take 5.0 g of the pre-emulsion and an aqueous solution of 0.1 g of ammonium persulfate dissolved in 3.0 g of water and add them to the reactor, stir and keep warm for 30 min; The remaining pre-emulsion was dripped into the reactor within 3 hours while keeping stirring and constant temperature. After the addition was completed, the reaction was kept warm for 1 hour and then cooled to room temperature. The reaction product was washed with water and ethanol for 3 times respectively, and filtered to obtain modified zinc oxide nanoparticle wet powder. The wet powder was placed in an oven and baked at 70 °C for 10 hours to obtain dry powder. The dry powder was ground with an agate mortar to obtain modified zinc oxide nanoparticles.

6. A modified zinc oxide nanoparticle, characterized in that Prepared according to any one of claims 1 to 5.

7. Use of the modified zinc oxide nanoparticles according to claim 6 as a formaldehyde removal agent, which has a high-efficiency and long-lasting formaldehyde removal effect.

Citation Information

Patent Citations

  • Formaldehyde removal agent

    CN113769549A

Cited By

  • Composition for anti-floating two-component tile adhesive, preparation method and application of anti-floating two-component tile adhesive

    CN122562432A